2022
DOI: 10.1136/jnis-2022-019220
|View full text |Cite
|
Sign up to set email alerts
|

Derivo embolization device for intracranial aneurysms: a Spanish multicenter retrospective study

Abstract: BackgroundFlow diverters have emerged in recent years as a safe and effective treatment for intracranial aneurysms, with expanding indications. The Derivo embolization device (DED) is a second-generation flow diverter with a surface finish that may reduce thrombogenicity. We report our multicenter experience evaluating its safety and efficacy.MethodsWe retrospectively analyzed all patients treated with the DED in eight centers in Spain between 2016 and 2020. Demographics, clinical data, procedural complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the present study, major ischemic stroke occurred in 2%, which is lower than reported in most studies of the PED. Similarly, major complications for Derivo were 5% in the Trivelato study, 4% in the Pinana study, 2% in the Lourenco study, and 3% in the Taschner study [14,16,33,34].…”
Section: Safetymentioning
confidence: 89%
“…In the present study, major ischemic stroke occurred in 2%, which is lower than reported in most studies of the PED. Similarly, major complications for Derivo were 5% in the Trivelato study, 4% in the Pinana study, 2% in the Lourenco study, and 3% in the Taschner study [14,16,33,34].…”
Section: Safetymentioning
confidence: 89%